Analysis of electronic navigational charts in order to enhance the safety of navigation - Igor KARNIČNIK (Transport Problems, 2012)
Navigational charts were, are and will probably be the most important aid to navigation on the ship's bridge. Paper charts have already been used for decades and now electronic ones are joined with the help of modern computer technology. The paper presents different types of navigational charts, electronic charts systems, their importance for safety of navigation, and the type of charts navigators can or should carry on board their ships.